Characterization of Two Wheat-Thinopyrum ponticum Introgression Lines With Pyramiding Resistance to Powdery Mildew - Li, Mingzhu; Yuan, Yuanyuan; Ni, Fei; Li, Xingfeng; Wang, Honggang; Bao, Yinguang (Frontiers in Plant Science, 2022)
Powdery mildew is one of the most devastating foliar diseases in wheat production. The wild relative Thinopyrum ponticum (2n = 10x = 70) has been widely used in wheat genetic improvement due to its superior resistance to both biotic and abiotic stresses. In the present study, two wheat-Th. ponticum introgression lines named SN0293-2 and SN0293-7 were developed from the progenies of a cross between the octoploid Trititrigia SNTE20 and common wheat, including the elite cultivar Jimai 22. They had a novel powdery mildew resistance gene (temporarily named PmSN0293) putatively from Th. ponticum pyramided with Pm2 and Pm52, exhibiting excellent Pm resistance at both the seedling and adult stages. Sequential GISH-FISH detected no signal of Th. ponticum in these two lines but a pair of T1BL·1RS in SN0293-2. Chromosomal structural variations were also observed obviously in SN0293-2 and SN0293-7. Through the Wheat 660K SNP array, 157 SNPs, 134 of which were on 6A, were found to be specific to Th. ponticum. Based on the data combined with DNA re-sequencing, seven specific markers, including one CAPS marker on 2B and six CAPS and Indel markers on 6A, were developed, confirming their wheat-Th. ponticum introgression nature. Furthermore, the two lines displayed positive plant height and produced more kernels and higher 1000-grain weight. Excellent resistance with desirable agronomic traits makes them valuable in wheat breeding programs.